Вплив соціально-економічної політики на соціальну безпеку та рівень життя населення України - Гнибіденко, І.Ф. (Інститут демографії та соціальних досліджень НАН України, 2006)
В статье рассмотрены основные вопросы влияния социально-экономической политики на состояние социальной безопасности и уровень жизни населения Украины. Освещен научный поиск путей упреждения социальных угроз человеку, обществу, государству и улучшения качества действующих социальных стандартов и нормативов. The main directions of the national economy development in correspondence with the social security level and living standards in Ukraine are considered. The results of scientific research on prevention of social threats for the man, society and state as well as improvement of quality of current social criteria are presented.